Development and validation of a new code for longitudinal train dynamics simulation. (March 2021) - Bosso, Nicola; Magelli, Matteo; Zampieri, Nicolò
Longitudinal train dynamics have a significant impact on both safety and performance of railway systems. Numerical simulation of long heavy haul trains can thus provide essential information for the development of diagnostic and signaling systems as well as coupling elements and braking systems. Long trains are usually modeled by considering only the longitudinal degree of freedom and by adding extra resistant forces to represent the track curvature and gradients. The prediction of in-train forces represents the most critical aspect in modeling the longitudinal dynamics of long trains made up of several vehicles. In fact, coupling elements have non-linear force–deflection characteristics, with different behavior in loading and unloading states, thus featuring a hysteretic loop. Look-up tables storing data from experimental tests are generally used to model these elements; however, other strategies, such as fitting curves and white-box models are witnessed in the literature. Recently, an international benchmarking of longitudinal train dynamics simulator was established in order to compare the output results obtained by different models with the same input data. The research group from Politecnico di Torino performed the simulations using the multibody software Simpack, but computational inefficiencies and numerical divergences occurred. To overcome these issues, a new dedicated in-house code was developed in the MATLAB environment. The paper focuses on the description of this new code and its validation, which was carried out by performing the simulations according to the benchmark inputs and comparing the results with the outputs from the other participants.